Prochlorococcus, Synechococcus, and picoeukaryotic phytoplankton abundances in the global ocean - Visintini Adomaitis, Natalia Soledad (2021)
Marine picophytoplankton is the most abundant photosynthetic group on Earth; however, it is still underrepresented in dynamic ecosystem models. Major constraints for understanding its role in the ecosystem at a global scale are sparse data and lack of a baseline description of its distribution. Here, we present three datasets to assess the global abundance of the principal groups of picophytoplankton, Prochlorococcus, Synechococcus, and picoeukaryotic phytoplankton: (1) a compilation of 109,045 field observations with ancillary environmental data, (2) a global monthly climatology of 1° grids from 0 to 200 m, and (3) four climate scenarios projections, from the Coupled Model Intercomparison Project 5, spanning years 1901 to 2100. Together this set of observational and modeled data can improve our understanding of the role of picophytoplankton in the global ecosystem.